The Use of Virus Models to Improve Biology Learning Outcomes of Virus Body Structure - Puspani Bandrang (Pinisi Journal of Education and Management, 2022)
This Classroom Action Research aims to describe the improvement of Biology learning outcomes in class X IPA 3 SMA Negeri 1 Balikpapan after applying the use of the virus model to the material structure of the virus body. The object of the research is the students of class X IPA 3, with a total of 35 students consisting of 17 male students and 18 female students. The method used is two cycles starting with a pre-cycle. Each cycle consists of four stages of activities, namely: (1) planning, (2) implementing actions, (3) observing and evaluating and (4) analyzing and reflecting. The results showed that in the pre-action there were 40% of students who completed and 60% who had not; in the first cycle there are 62.86% of students who have completed and 37, 14% of students who have not completed and in the second cycle there are 85.71% of students who have completed and 14.29% of students who have not. The discussion states that learning by using the virus model can improve the learning outcomes of biological material on the structure of the virus body, which is indicated by the percentage increase that occurred since pre-action, cycle I and cycle II. This is very relevant to the opinion of previous studies. The conclusions obtained in this study are that through the use of the virus model in biology learning in class X IPA 3 SMA Negeri 1 Balikpapan can increase student learning outcomes by 45.71%, namely: in the first cycle by 22.86% and in the second cycle by 22 ,85%.